Edukasi Pemberian Buah Naga Untuk Pencegahan Anemia Pada Remaja Putri Di Puskesmas Pringsewu - Yetty Dwi Fara; Elsy Juni Andry Karini; Wulan Dari; Nopi Anggista Putri; Ghina Hamidah Hanun; Hindun Arfiani; Indah Wiridawati; Leni Rolimah; Lutfiatul Ulva; Putriana Windarti; Saefinaqia Saefinaqia; Siti Marfuah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Anemia is a global health problem that commonly affects adolescent girls, primarily due to iron deficiency. This condition may lead to growth disorders, impaired reproductive health, and decreased concentration and academic performance. Preventive efforts can be carried out through the consumption of dragon fruit (Hylocereus polyrhizus), which is rich in iron, vitamin C, and antioxidants that play an important role in hemoglobin formation. This community service activity aimed to increase adolescent girls’ knowledge about anemia and to evaluate the benefits of combining dragon fruit with Fe tablets in preventing anemia. The study applied an observational analytic method with a pretest-posttest design, involving 38 adolescent girls at Pringsewu Public Health Center on August 8, 2025. Data were collected using a questionnaire consisting of 15 questions on anemia, hemoglobin level examination, and an intervention in the form of health education using leaflets combined with the practice of consuming dragon fruit and Fe tablets for seven days. The results showed an increase in knowledge after the education session, as well as an improvement in hemoglobin levels. Before the intervention, the lowest hemoglobin levels were 9.1 g/dl and 11.5 g/dl, which increased to 10.2 g/dl and 11.5 g/dl after the intervention. These findings indicate that the combination of dragon fruit and Fe tablets is effective in improving hemoglobin levels and has the potential to prevent iron-deficiency anemia. Dragon fruit also contains phytoalbumin antioxidants, fiber, calcium, phosphorus, vitamin C, and B2, which support immunity and overall health. Health education combined with the consumption of dragon fruit and Fe tablets is an effective strategy for preventing anemia in adolescent girls. It is recommended that this program be implemented sustainably with the support of schools and health workers.